The Effectiveness of Pre-Listening Activities in Enhancing Junior High School Students’ Listening Comprehension - Eiffel Fairuz Nawwar Putra Raharjo; Him'mawan Adi Nugroho (SM Institute, 2026)
The main objective of this research is to investigate if junior high school students' listening comprehension ability is significantly affected by the use of pre-listening activities. A quasi-experimental approach was applied in this quantitative study, utilizing both control and experimental classes. Sixty-four eighth-graders from Junior High School Muhammadiyah 2 Taman (academic year 2025/2026) were selected as participants through a purposive sampling technique. These learners were separated into two equal segments: 32 students in the control group and another 32 in the experimental group. To gather the required data, a 25-item multiple-choice listening test was administered. Before undertaking the actual listening tasks, vocabulary previews, visual aids, and guided questions were given to the experimental class. Meanwhile, standard listening lessons without initial preparation were delivered to the control group. The collected scores were evaluated with inferential statistics, specifically applying an independent samples t-test via IBM SPSS Statistics version 27. Based on the findings, a higher post-test mean score was achieved by the experimental group (M = 83.25) compared to the control group (M = 75.25). Furthermore, a clear statistical difference between the two classes was confirmed by the significance value of p < .001 (Sig. 2-tailed < 0.05). A large impact was also revealed by the effect size calculation, which resulted in a Cohen’s d of 1.202. To summarize, the findings suggest that the application of pre-listening strategies positively influenced the learners' listening comprehension scores in this study.